A Survey on Technologies Used in Glucose Monitoring for Diabetic Patients (International Journal of Innovative Research in Computer Science & Technology, 2024)
In the recent years, there has been a great  improvement of technology in engineering as well as  medical industries. Even though the technology has  increased in the medical field, the patient’s waiting  time in hospitals and emergency appointments is  extremely costlier nowadays. In the modern lifestyle  many people are susceptible to Diabetes Mellitus  (DM).The management and monitoring of DM is a  challenge for the diabetic patients. This paper surveys  about the various methods used in self-monitoring of  blood glucose levels pervasively. The devices used for  self-monitoring of glucose level are also discussed in  this survey. These devices are very useful in the present  busy life scenario. The major disadvantage of these  devices is that they are expensive and cannot afford by  all diabetic patients. An idea can proposed which  involves the preparation of the kit which directly  calculates the glucose level and automates with an alert  message that includes the diet control,exercise control and medication control.
Keywords: Diabetes Mellitus (DM); Glucose level; self monitoring; Devices; Internet of Things (IoT)